Empiricism without dogmas: a comment on Quine’s critique to logical positivism - Hamma, Alioscia (BORNH Bulletin of Regional Natural History, 2022)
In his celebrated essay Two Dogmas of Empiricism[1], Quine rejects the traditional postulates of logical positivism, namely the analytic- synthetic distinction and the doctrine of verifiability of singular statements. A first consequence is the impossibility of invalidating any statement and a form of holism. The second consequence is pragmatism. Quine’s arguments echo those of some cultural anthropology. We remark on the role of Philosophy as activity.